1988
DOI: 10.1126/science.241.4862.196
|View full text |Cite
|
Sign up to set email alerts
|

Irregular Recurrence of Large Earthquakes Along the San Andreas Fault: Evidence from Trees

Abstract: Old trees growing along the San Andreas fault near Wrightwood, California, record in their annual ring-width patterns the effects of a major earthquake in the fall or winter of 1812 to 1813. Paleoseismic data and historical information indicate that this event was the "San Juan Capistrano" earthquake of 8 December 1812, with a magnitude of 7.5. The discovery that at least 12 kilometers of the Mojave segment of the San Andreas fault ruptured in 1812, only 44 years before the great January 1857 rupture, demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 8 publications
3
78
0
Order By: Relevance
“…Similar aperiodic behavior was reported along the Dead Sea Fault zone [Marco et al, 1996]. Other examples of long-term analysis of seismic activity using historical catalogs [Ambraseys, 1989;Vere-Jones and Ozaki, 1982;Xu and Deng, 1996;Goes, 1996], paleoseismologic data [Jacoby et al, 1998;Grant and Sieh, 1995;Marco et al, 1996;Wells et al, 1999], geomorphological data [Ritz et al, 2003], or geodesic and geologic data [Friedrich et al, 2003] show that periods of activity can alternate with periods of quiescence along a single fault or a group of faults and that many fault zones exhibit temporal earthquake clustering [Pirazzoli et al, 1996]. These observations suggest that a representative record of the long-term behavior of a fault zone may require a knowledge of all strong earthquakes over period exceeding 10,000 years [ Van der Woerd et al, 2002].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Similar aperiodic behavior was reported along the Dead Sea Fault zone [Marco et al, 1996]. Other examples of long-term analysis of seismic activity using historical catalogs [Ambraseys, 1989;Vere-Jones and Ozaki, 1982;Xu and Deng, 1996;Goes, 1996], paleoseismologic data [Jacoby et al, 1998;Grant and Sieh, 1995;Marco et al, 1996;Wells et al, 1999], geomorphological data [Ritz et al, 2003], or geodesic and geologic data [Friedrich et al, 2003] show that periods of activity can alternate with periods of quiescence along a single fault or a group of faults and that many fault zones exhibit temporal earthquake clustering [Pirazzoli et al, 1996]. These observations suggest that a representative record of the long-term behavior of a fault zone may require a knowledge of all strong earthquakes over period exceeding 10,000 years [ Van der Woerd et al, 2002].…”
Section: Discussionmentioning
confidence: 77%
“…[3] Historical earthquake records [Ambraseys, 1989;Vere-Jones and Ozaki, 1982;Xu and Deng, 1996;Goes, 1996] and paleoseismologic data [Jacoby et al, 1998;Grant and Sieh, 1995;Marco et al, 1996;Wells et al, 1999] have, however, shown that earthquake recurrence time and earthquake-related slip on a given fault can show great variations. These variations are yet poorly understood though several models predict irregular behavior [Bak and Tang, 1989;Carlson and Langer, 1989;Ben-Zion, 1996;Shaw and Rice, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, tree rings have extensively been used to study century-old earthquakes along the San Andreas Fault in California or in the Seattle region (Jacoby et al, 1988(Jacoby et al, , 1992Jacoby, 1997). More recently, Bekker (2004) has analyzed spatial differences in the response of trees to normal faulting in relation with the Hebgen Lake earthquake.…”
Section: What Natural Hazards Processes Are Analyzed With Tree Rings?mentioning
confidence: 99%
“…For example, the sudden and pronounced suppressions following defoliation are often an integral part of reconstructing insect outbreak events (Swetnam et al 1985;Veblen et al 1991b;Speer et al 2001;Davis et al 2007). Suppression criteria have also been applied to identify the frequency of canopydamaging storm events in the forests of the eastern United States (Orwig et al 2001;Lafon and Speer 2002), and root-damaging earthquakes along the San Andreas Fault (Jacoby et al 1988). In these situations, release often represents a growth rebound that occurs several years after the damage has occurred.…”
Section: Introductionmentioning
confidence: 99%